On Access to University Information Resources - Konvit, Martin (Communications - Scientific letters of the University of Zilina, 2012)
Paradigm of access to information resources has been radically changed due to developments in ICT. While old paradigm said that “University is buildings surrounding the library” under new paradigm databases of digital information sources are the heart of University. Model of building university digital information sources and method of access to them is presented in this contribution with the stress put on legislative aspects.